Situation Report: Bulgaria, 12 August 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. An Assessment of the July BCP Plenum / by Stephen Ashley Passport Law Reforms Still Awaited / by Ana Ivanova Major Problems in the Schooling of Moslem Children / by Stephen Ashley Party Daily Calls for Dramatic Liberalization of Policy toward Rock Music / by Stephen Ashley